Lions and tigers and murder, oh my [large type] - Swanson, Denise (Swanson, Denise. Devereaux's Dime Store mystery., 2018)
"Opening a dime store in her hometown of Shadow Bend, Missouri, Devereaux "Dev" Sinclair left the wilds of city life behind her. But she soon discovers that even rural life can be beastly when she becomes embroiled in the first case of the handsome private investigator renting the office space on the second floor above her store"--